A new model of agent spawning and mobility - Alshaki O.T.; Ahmad M.S.; Mahmoud M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cloning; Distributed computer systems; Genetic engineering; Multi agent systems; Robotics; Agent architectures; Agent mobilities; Mobile agent technology; Mobility model; Mobile agents